Impactos da cultura na economia da Bahia: participação no gasto turístico e consumo de residentes e governo - Burman, Grazia (Revista Turismo em Análise, 1998)
This study presents important cultural production and consuming aspects in the economy of Bahia State. The metodology used, considered the impactof cultural gross domestic product, which represented in 1966 - 4,4% of the total gross domestic product of Bahia State. The incremental of tourism activitie in these areas provided a substancial improvements of life condictions for local residents and govemment incame through new jobs generation and local consuming in crease.